Merangkai Perbedaan, Merayakan Perdamaian: Telaah Konflik antara Pribumi dan Etnis China - Ulfah Fajarini (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2005)
The social conflict between natives and ethnic Chinese seems to have become a historical destiny of this country. Even before independence, conflicts between the two had already occurred. Various efforts have been made to stop the conflicts, which often ended in violence, but the conflicts themselves never seemed to cease. This paper seeks to offer an approach to reorganize the potential conflicts into positive potentials by examining the socio-historical aspects that cause the points of contention between natives and ethnic Chinese. From there, a nation-building that is aspired to is not just a symbol of sovereignty but is truly felt by all citizens without being trapped by ethnic, tribal, racial, or religious barriers.